Institutional barriers to business entry in advanced economies - Kosi, Tanja; Bojnec, Štefan (Journal of Business Economics and Management, 2013)
The paper empirically examines the impact of freedom from regulation in different institutional areas on business entry rate in 10 Organisation for Economic Co-operation and Development countries over the period 1995–2007. Employing the feasible generalized least squares econometric approach, it discloses a positive association between business entry and the overall institutional freedom. Economic freedom in different institutional areas, however, does not appear to have the same importance for business entry. Institutional freedoms that are the most beneficial for business creation are product market freedom, property rights freedom, and freedom from corruption. This implies that simple and inexpensive administration procedures, competitive product markets, and transparent and effective legal/judicial system help promote business creation. Business entry is also positively associated with macroeconomic prosperity in terms of employment growth and the development of information and communication technology industry.